Efficacy of the Mulligan technique on subacromial space in patients withshoulder impingement syndrome - Mohammed, Amal H.; Mahmoud, Noha A.; Abd El-Naeem, Mohammed A.; Abd El-Azeim, Alshaymaa S. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. To estimate the effectiveness of the Mulligan technique for the shoulder complex on the subacromial space,shoulder ROM, pressure pain threshold, and function of the shoulder in the impingement syndrome patient.Methods. Thirty patients who suffered from shoulder impingement syndrome were at random allocated into two groups; theexperimental group received shoulder complex mobilization with movement plus conventional therapy, and the control groupreceived conventional treatment. All patients were examined by ultrasonography for subacromial space, shoulder range of motion using a digital goniometer, electronic algometry for pressure pain threshold, and the Quick DASH for a difficulty level involvedin carrying out several physical activities.Results. In comparison to group B post-treatment, there were statistically significant improvements in the subacromial space(p > 0.004), flexion and abduction ROM, PPT of the biceps and supraspinatus (p > 0.001), and a significant reduction in the quickDASH (p > 0.001).Conclusions. Shoulder complex mobilization with movement plus conventional therapy improved subacromial space, shoulderROM, pressure pain thresholds, and function more than conventional therapy alone in shoulder impingement syndrome patients
Keywords: shoulder impingement syndrome; Mulligan technique; sub-acromial space; shoulder complex